Attitudes toward euthanasia and related issues among physicians and patients in a multi-cultural society of Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammad Fauzi; Shahar, Mohammad Arif; Ab Rahman, Jamalludin; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Mohamad Shah, Azarisman Shah (Wolters Kluwer India Pvt. Ltd., 2014)
Introduction: Due to globalization and changes in the health care delivery system, there has been a gradual change in the attitude of the medical community as well as the lay public toward greater acceptance of euthanasia as an option for terminally ill and dying patients. Physicians in developing countries come across situations where such issues are raised with increasing frequency. As euthanasia has gained world‑wide prominence, the objectives of our study therefore were to explore the attitude of physicians and chronically ill patients toward euthanasia and related issues. Concomitantly, we wanted to ascertain the frequency of requests for assistance in active euthanasia. Materials and Methods: Questionnaire based survey among consenting patients and physicians. Results: The majority of our physicians and patients did not support active euthanasia or physician‑assisted suicide (EAS), no matter what the circumstances may be P < 0.001. Both opposed to its legalization P < 0.001. Just 15% of physicians reported that they were asked by patients for assistance in dying. Both physicians 29.2% and patients 61.5% were in favor of withdrawing or withholding life‑sustaining treatment to a patient with no chances of survival. Among patients no significant differences were observed for age, marital status, or underlying health status. Conclusions: A significant percentage of surveyed respondents were against EAS or its legalization. Patient views were primarily determined by religious beliefs rather than the disease severity. More debates on the matter are crucial in the ever‑evolving world of clinical medicine.